2023
DOI: 10.25259/jnrp_76_2023
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of stroke admissions at a rural Nigerian tertiary health facility: Insights from a single-center study

Abstract: Objectives: This research intended to examine the demographic and clinical attributes of stroke admissions in a rural Nigerian hospital. Materials and Methods: A retrospective analysis of stroke admissions was conducted over 1 year. All necessary data were obtained from patients’ records and SPSS was employed for data analysis. P < 0.05 was deemed significant. Results: There were 52 stroke cases, accounting for 5.9% of medical admissions. The patients’ mean age was 62.81 ± 12.71 years, while females con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…In Africa, data available within the past 10 years showed that stroke has a yearly incidence rate of up to 316 per 100,000, a prevalence of up to 1,460 per 100,000, and a 3-year mortality rate greater than 80% (Akinyemi, et al, 2021). In Nigeria between the last two decades, 30-day case fatality rates ranging from 21.2% to 40% was reported (Erameh, Emorinken, & Akpasubi, 2023;Ekeh, et al, 2015;Mohammedm et al, 2021). The Global Stroke Factsheet8 brought out in 2022 indicated that the likelihood of having a stroke in one's lifetime has increased by 50% over the last decade and 1 in 4 people is predicted to have a stroke in their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, data available within the past 10 years showed that stroke has a yearly incidence rate of up to 316 per 100,000, a prevalence of up to 1,460 per 100,000, and a 3-year mortality rate greater than 80% (Akinyemi, et al, 2021). In Nigeria between the last two decades, 30-day case fatality rates ranging from 21.2% to 40% was reported (Erameh, Emorinken, & Akpasubi, 2023;Ekeh, et al, 2015;Mohammedm et al, 2021). The Global Stroke Factsheet8 brought out in 2022 indicated that the likelihood of having a stroke in one's lifetime has increased by 50% over the last decade and 1 in 4 people is predicted to have a stroke in their lifetime.…”
Section: Introductionmentioning
confidence: 99%